The palladium/norbornene-catalyzed ortho-silylmethylation reaction: a practical protocol for ortho-functionalized one-carbon homologation of aryl iodides. Issue 97 (17th November 2016) - Sui, Xianwei; Ding, Linlin; Gu, Zhenhua
Abstract : We reported the introduction of a functionalized methyl group into the ortho -position using the Catellani reaction. Abstract : A palladium/norbornene-catalyzed ortho -silylmethylation reaction using of (iodomethyl)cyclohexyloxydimethylsilane as the electrophile was reported. The ((cyclohexyloxy)dimethylsilyl)methyl group was readily oxidized using the Fleming–Tamao process or by ceric ammonium nitrate to give benzylic alcohol derivatives. This method was successfully applied in a concise synthesis of a biaryl analogue of schisandrins.